PEOPLE AND TRADITIONAL COMMUNITIES: CONTRIBUTIONS TO ANOTHER DEVELOPMENT - Maria Narciso Rocha de Paula, Andréa; Anaya, Felisa; Cristina Barbosa de Brito, Isabel; Helena de Souza Ide, Maria; Soares Barbosa, Rômulo; Gawora, Dieter (Revista Desenvolvimento Social, 2020)
The joint condition of peoples and traditional communities and their public recognition at national and international levels is presented differently in a context of dispossession by globalized capital. The different forms of appropriation of social spaces, impose a kind of economic development that causes the degradation of natural and social environments, the disruption of lifestyles in place, and increases the sociospatial inequalities and the loss of territorial control. In this sense, it is necessary to discuss another possible development that includes the social agents who have another logic of appropriation and use of the environment, contributing their knowledge and their local practices For both, the analysis of social and environmental conflicts through dialogue between different actors and societal contexts was realized.In this perspective, another development by traditional peoples and communities is presented in the "Declaration of Montes Claros," result of discussion between universitytraditional communities, social movements and civil organizations